MPASI SEBAGAI UPAYA PENCEGAHAN STUNTING - Siska Ningtyas Prabasari; Triani, Yuyun (P3M Universitas Aisyiyah Surakarta, 2024)
Mother's milk companion food (MP-ASI) is a complementary food to meet the nutritional needs of infants under five after six months of age. In practice there are still many Indonesian people giving MP-ASI at less than six months. This is what causes high incidence of infections such as diarrhea, airway infections, allergies to growth disorders. The high incidence of infection has an impact on the decline of the health of infants toddlers so that nutritional needs are not optimal that lead to stunting cases. Therefore, a promotive and preventive effort is needed by providing education the importance of giving MPASI, especially in the Golden Age period aged 6-24 months so that stunting problems are not a problem that always haunts children's health in Indonesia. It is hoped that this effort can significantly reduce stunting cases. The results of the preliminary study were obtained by most mothers who have toddlers in Jumapolo Karanganyar Regency lack understanding of the administration and processing of MPASI. Methods: The method carried out in this community service activity is in the form of giving education around MPASI followed by giving a questionnaire to find out the level of mother's knowledge about the importance of giving MP-ASI in meeting the nutritional needs of her child. Results: Participants in this community service as many as 30 mothers who have children aged 6 months-24 months and come to the posyandu Jumapolo Karanganyar Regency with only 79 % of mothers understand the importance of MP-ASI but after being given education the mother's understanding increased 94 %. Conclusion: Community service in the form of providing education to mothers under five is carried out well and active participants discuss in these activities. In the future it is expected that community service can be carried out by practicing MPASI making.